2015
DOI: 10.1007/s11816-015-0361-8
|View full text |Cite
|
Sign up to set email alerts
|

Monthly metabolic changes and PLS prediction of carotenoid content of citrus fruit by combined Fourier transform infrared spectroscopy and quantitative HPLC analysis

Abstract: This work examined the potential of Fourier transform infrared spectroscopy (FT-IR) spectroscopy and high-performance liquid chromatography (HPLC) analysis in evaluating metabolic changes during ripening of citrus fruit. Further, the feasibility of prediction modeling of carotenoid content by multivariate statistical analysis combined with FT-IR spectral and HPLC data was examined without additional HPLC analysis. FT-IR spectra of citrus (Citrus unshiu Marc. cv. Miyagawa) fruit peels and flesh were measured at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…As well, the results indicated that total carotenoids, flavonoids, and phenolic compounds in citrus cultivated under different conditions differed even in the same citrus cultivar. The results were in accord with other reports that showed large differences in the concentration of functional compounds such as total phenolic content in different citrus cultivars [3][4][5][6][7].…”
Section: Contents Of Total Carotenoids Flavonoids and Phenolic Compsupporting
confidence: 92%
See 2 more Smart Citations
“…As well, the results indicated that total carotenoids, flavonoids, and phenolic compounds in citrus cultivated under different conditions differed even in the same citrus cultivar. The results were in accord with other reports that showed large differences in the concentration of functional compounds such as total phenolic content in different citrus cultivars [3][4][5][6][7].…”
Section: Contents Of Total Carotenoids Flavonoids and Phenolic Compsupporting
confidence: 92%
“…A model for predicting citrus fruit contents on the carotenoid has been reported [4]. According to carotenoid species, R 2 values were 0.73-0.91.…”
Section: Pls Regression Modeling For the Contents Prediction Of Totalmentioning
confidence: 99%
See 1 more Smart Citation